Evaluation of wheat Genotypes for heat stress and disease resistance in multiple environments of Bangladesh (Bangladesh Journal of Agriculture, 2023)
Twenty-seven advanced lines including three exiting varieties (BARI Gom 21, BARI Gom 32 and BARI Gom 33) were evaluated in alpha lattice design with two replications at Bangladesh Wheat and Maize Research Institute, Dinajpur and regional stations at Joydebpur, Jashore and Rajshahi under irrigated timely sown (ITS) and irrigated late sawn (ILS) conditions. The objective of the study was to find out the heat-tolerant wheat lines for future breeding programme to develop heat-tolerant wheat varieties. The genotypes were evaluated for phenological variation such as heading and maturity, yield and yield components, disease reaction, sterility, visual grain quality, etc. The results showed that the highest grain yield (5951 kg ha-1) was recorded with genotype BAW 1415 at Dinajpur under ITS condition and the lowest grain yield (1923 kg ha-1) was observed in BAW 1416 at Rajshahi under ILS condition. Considering the overall performances, genotypes BAW 1402, BAW 1403, BAW 1406, BAW 1407, BAW 1408, BAW 1411, BAW 1422 and BAW 1425 performed better. Considering disease infestation, genotypes BAW 1374, BAW 1393, BAW 1394, BAW 1397, BAW 1399 and BAW 1401 showed a good level of resistance to both leaf rust (LR) and wheat blast (WB). These genotypes could be selected for future breeding programmes to develop heat-tolerant and diseases resistance varieties.Bangladesh J. Agri. 2022, 47(2): 1-16